Food Security and Diet Among American Indians in the Midwest - Berryhill, Kelly (J Community Health, 2018)
The purpose of this study was to determine levels of food security among American Indians (AI) living in the Midwest and possible correlations between food security levels and various health outcomes, diet, and demographic variables. This study used a cross-sectional design to determine health behaviors among AI. Participants (n= 362) were recruited by AI staff through various cultural community events in the Midwest, such as powwows and health fairs. Inclusion criteria included the following: age 18 years or older, self-identify as an AI, and willing to participate in the survey. Of all participants, 210 (58%) had either low or very low food security, with 96 in the very low category (26.5%). Participants with very low food security tended to have significantly more chronic conditions. Additional significant differences for very low food security existed by demographic variables, including having no insurance (p<0.0001) or having a regular primary care provider (p=0.0354). There was also a significant difference between food security levels and the consumption of fast food within the past week (p-value = 0.0420), though no differences were found in fruit and vegetable consumption. AI in our sample had higher levels of food insecurity than those reported in the literature for other racial/ethnic groups. AI and non-Native health professionals should be aware of the gravity of food insecurity and the impact it has on overall health. Additional research is needed to determine specific aspects of food insecurity affecting different Native communities to develop appropriate interventions.